Adductor canal block with a suture‐method catheter – A parallel or perpendicular approach?. Issue 4 (6th December 2018) - Lyngeraa, Tobias S.; Rothe, Christian; Grevstad, Ulrik; Lundstrøm, Lars H.; Lange, Kai H. W.
Abstract: Background: We performed a randomised blinded pilot study in 16 healthy volunteers to assess whether placing a suture‐method catheter in the adductor canal is feasible with two different insertion techniques. Methods: Each volunteer had a suture‐method catheter placed approximately halfway between the superior anterior iliac spine and base of the patella in both legs. Catheters were placed using a parallel technique in one leg and a perpendicular technique in the other leg, according to randomisation. 15 mL lidocaine 1% was injected in each catheter. Successful placement was defined as loss of cold sensation in the saphenous area 30 min after injection. Volunteers were sent home and returned the following day and another dose of lidocaine (15 mL, 1%) was injected through the catheters. Catheter displacement distance was assessed by ultrasound and cold sensation was assessed. In case of preserved cold sensation, we attempted to reposition the catheter with a subsequent injection of lidocaine and reassessment of cold sensation. Results: All primary placements were successful using the perpendicular approach (100%; 95% CI 81%‐100%) whereas one placement failed using the parallel approach (94%; 95% CI 72%‐99%). Three catheters placed using the perpendicular approach were displaced on day 2, compared to one catheter placed with the parallel approach. Displacement distance was highly variable. All catheters, except one, could be repositioned. Three volunteers reported transient sensory deficits lasting approximately 6‐8 weeks. Conclusion: The suture‐method catheter can be placed in the adductor canal with high success rates for initial placement with both techniques.